The emotional politics of territorio: women's resistance at the Isthmus of Tehuantepec, Oaxaca, Mexico - Philipp, Rosa (Geographica Helvetica, 2025)
Using the example of resistance to a mega-project in southern Mexico, this paper shows how the emotional connections between bodies and land are used as political instruments in resistance movements. The Interoceanic Corridor is currently being built on the Isthmus of Tehuantepec, which leads to shifts in territorial organisation. The resistance movements that have emerged against (neo-)extractivist infrastructure projects in Latin America use the concept of territorio in their attempt to defend their lands. This paper argues that emotional attachments to territorio have so far been overlooked in debates on territorio and yet are key, as they lie at the centre of territorial identities and are a source of life. Based on interviews with women who understand themselves as defenders of territorio, I investigate the emotional link to territorio using the concept of cuerpo–territorio. The paper shows how women politicise and use their emotional link strategically in their practices of resistance.